EXPLORING THE ROLE OF BLOCKCHAIN AND CRYPTOCURRENCY IN RESHAPING GLOBAL TRADE: A BIBLIOMETRIC ANALYSIS - Hendricus Jerricho Van Schoggers; Suyanto Suyanto; Olivia Tanaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In the rapidly evolving digital era, technological transformation has become a critical factor in accelerating and streamlining global trade. Blockchain and cryptocurrency have emerged as innovations with significant potential to revolutionize cross-border transactions by offering fast, intermediary-free methods of transaction. Blockchain ensures transparency, security, and efficiency in managing global supply chains and business transactions, while cryptocurrency enables faster and cheaper cross-border payments, eliminating delays and high fees associated with traditional banking systems. The purpose of this study is to explore the role of blockchain and cryptocurrency in reshaping global trade, analyze patterns and trends in the global trade digital transformation literature, and identify the challenges and opportunities faced by these technologies in the context of international trade. This study uses a bibliometric approach to analyze relevant literature, resulting in four main clusters: Green (Global Trade and Supply Chain), Blue (Ethereum Blockchain and Challenge), Red (Market and Currency), and Yellow (Role and Example). The findings suggest that blockchain and cryptocurrency can enhance the efficiency, security, and transparency of international trade; however, challenges such as cryptocurrency price volatility, security issues, and limited technology adoption still need to be addressed to fully realize the potential of these technologies.